2023
DOI: 10.7759/cureus.38489
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Learning Outcomes in Cardiopulmonary Resuscitation (CPR) and/or Automated External Defibrillator (AED) Training for Laypeople in Face-to-Face, Online, and Mixed Training Methods: An Integrative Literature Review

Abstract: Cardiovascular diseases and cardiac arrest (CA) are the main causes of death worldwide. This review aims to identify publications on the learning outcomes for the use of an automated external defibrillator (AED) and/or cardiopulmonary resuscitation (CPR) to train laypeople (LP), the method of training used, the year of publication and their recommendations. We employed Miller's assessment pyramid to describe learning outcomes as knowledge, skills, and confidence. The methods of training are face-to-face, onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Only a small percentage of people living in rural communities are able to get timely access high quality healthcare (30). Some researchers employed simulationbased programs to train laypersons on the operation of AEDs delivered by drones in rural and difficult regions (31).…”
Section: Discussion Of Literature Datamentioning
confidence: 99%
“…Only a small percentage of people living in rural communities are able to get timely access high quality healthcare (30). Some researchers employed simulationbased programs to train laypersons on the operation of AEDs delivered by drones in rural and difficult regions (31).…”
Section: Discussion Of Literature Datamentioning
confidence: 99%
“…The participants' suggestions to include offline accessibility and reallife scenarios align with the principles of experiential learning [23][24]. By simulating authentic situations and providing hands-on experiences, the program caters to the needs of HCPs and LP operating AEDs in remote and rural areas [10].…”
Section: Theoretical Contributionsmentioning
confidence: 96%
“…For this purpose, the researchers conducted a literature review that revealed that mixed, face-to-face, and online training for AED use all yielded similar outcomes in terms of learning assessment, including selfconfidence, performance, skills, and knowledge acquisition for individuals with little or no prior experience with AEDs [10]. Based on these findings, it is reasonable to suggest that teaching HCPs and LP in R&R locations to use AEDs delivered by drones is a viable option.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations